Guadeloupe, Martinique, LKP, crise de 2009, crise économique, déclin économique : de crises en crises : la Guadeloupe et la Martinique - Michel Desse (Études Caribéennes)
The long strikes that paralyzed Guadeloupe and Martinique in 2009 are partly related to the crisis in the island economies. Agriculture is threatened by the new WTO negotiations that are unfavorable to exports of bananas and sugar. Tourism sector is also low. Under these conditions, unemployment and underemployment are difficult to accept when prices rise and development prospects are not really defined.